TEAM BASED LEARNING (TBL) DALAM PENINGKATAN PENGETAHUAN, HASIL BELAJAR DAN KERJASAMA : LITERATURE REVIEW - Islamarida, Rista (Jurnal EDUNursing, 2019)
ABSTRACTIncreasing learning outcomes in higher education programs, especially professional education nurses according to the KKNI level need to pay attention to the appropriate learning methods for their students. Some of the components needed in achieving the KKN level are knowledge and cooperation. The learning method that uses the Student Center Learning principle is Team Based Learning (TBL). The research method used is Literature Review. Data collection is done by writing keywords using Google Schoolar, Pubmed, and Proquest. With the keywords entered there were 2,653 articles which were then selected according to the inclusion and exclusion criteria so that 32 articles were obtained for review. From the results of the journal review, it was found that the TBL method had an effect on knowledge, critical thinking, and teamwork. The use of the TBL method is considered to be able to train students' independent abilities in learning, activeness in complex discussion and problem solving.Keyword : Team Based Learning, knowledge, critical thinking, teamwork